2016
DOI: 10.1016/j.mib.2015.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Fresh layers of RNA-mediated regulation in Gram-positive bacteria

Abstract: Bacterial regulatory RNAs have been defined as diverse classes of cis and trans elements that may intervene at each step of gene expression, from RNA and protein synthesis to degradation. Here, we report on a few examples from Gram-positive bacteria that extend the definition of regulatory RNAs to include 5' and 3' UTRs that also act as cis and trans regulators. New examples unveil the existence of cis and trans acting regulatory RNAs on a single molecule. Also, we highlight data showing that a key RNA chapero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 59 publications
0
31
0
Order By: Relevance
“…On the one hand, heterologous expression of diverse Hfq proteins in Salmonella showed that members of this family have an intrinsic propensity to bind sRNAs 96 . On the other hand, the collective results of Hfq studies in Gram-positive bacteria so far argue against the prominent sRNA-mRNA matchmaking function that is a hallmark in Gram-negative bacteria 97 .…”
Section: Hfqmentioning
confidence: 99%
“…On the one hand, heterologous expression of diverse Hfq proteins in Salmonella showed that members of this family have an intrinsic propensity to bind sRNAs 96 . On the other hand, the collective results of Hfq studies in Gram-positive bacteria so far argue against the prominent sRNA-mRNA matchmaking function that is a hallmark in Gram-negative bacteria 97 .…”
Section: Hfqmentioning
confidence: 99%
“…Cis-acting sRNAs form fully complementary interactions with their target mRNAs, whereas trans-acting sRNAs are only partly complementary to their partner mRNAs. In Gram-negative bacteria, the interaction between a trans-acting sRNA and its targets often relies on an RNA chaperone, such as Hfq, which promotes sRNA-mRNA duplex formation, whereas in Gram-positive bacteria, a role for Hfq in sRNA-mediated control is less clear [3].…”
Section: Hfq-binding Srnas -Recent Discoveriesmentioning
confidence: 99%
“…Limiting accessibility of the RBS is therefore a common mechanism for gene regulation that bacteria have exploited in many different ways. There are several other recent reviews of focusing on diverse aspects of this area . RNA structure can be quite dynamic, and RNA structures have evolved to interpret changing conditions within the cell.…”
Section: Regulation Of Translation In Response To Stimulimentioning
confidence: 99%